Teaching of history and school texts: the elementary course of history of Bolivia (1936-1944) by Antonio Díaz Villamil (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2021)
Historical school texts not only refer to the way of teaching history, but also to memory, its imaginaries and attitudes of a specific geographical context and historical period. The article develops a look at the main contributions in Bolivia on history teaching textbooks. Then the analysis of Antonio Díaz Villamil's Elementary Course in History textbook is presented. On the one hand, his career and the socio-historical context in which the four volumes were written are described; on the other, volume IV is analyzed from the interpretation, perception and historical orientation. The contribution of the article lies in making visible some criteria for the analysis of history textbooks.
Keywords: history teaching; textbook analysis; Bolivian history